Bacillus sp. strains and their inducible in vitro antagonism : a biochemical and molecular study (2018)
Discovering novel antibiotic substances from natural sources and revitalizing the pipeline for screenings of naturally sourced substances that could render new bioactive compounds, is a priority nowadays in the face of a world crisis of antimicrobial resistance. This research was focused on disclosing an observed antagonism system composed of Bacillus sp. strains producing inducible antimicrobial activity against the plant pathogen Ralstonia solanacearum, a widespread bacterium that causes bacterial wilt disease to a great variety of plant species, including many agriculturally important ones as are bananas. The inducible phenomenon was discovered during the screening of 1493 aerobic endospore forming bacteria against plant pathogens. It was observed that in the presence of the chemical compound Triphenyl Tetrazolium Chloride (TTC), which belongs to the group of synthetic compounds known as tetrazolium salts used to monitor cell respiration, Bacillus sp. strains produced inhibition zones against the bacterial plant pathogen and other pathogenic bacterial species, while in the absence of the compound they did not have any bioactivity. During biochemical characterization, it was evidenced that although the phenomenon was observable across several species of the order Bacillales, strains belonging to B. cereus, B. pumilus and B. subtilis were outstanding in their inducible antagonism potential, among other species tested. Besides, relevant traits revealed that other tetrazolium salts did not induce antagonistic activity and that the addition of antioxidant compounds did not reduce the inducible antagonistic activity. Also, R. solanacearum sensitivity to antibiotics was not increased by the addition of TTC and the inducible activity was independent of the presence of the pathogenic strain. In order to determine genes and pathways that were activated under TTC conditions, transcriptomic and metabolomics analysis were performed. Transcriptomic results revealed that specific pathways of the nitrogen metabolism, such as pyrimidines, purines and histidine biosynthetic routes, were 2 to 5 fold up-regulated in B. subtilis NCIB-3610 cells growing under TTC presence. On the other hand, metabolomic analysis showed that 28 specific compounds were either unique or 3 to 5 fold more abundant in active extracts obtained from inducible conditions, compared to non-induced controls. Data mining on public chemical databases, using intrinsic properties of the selected compounds, suggests that they mostly belong to chemical families of carbamates, imidazoles, pyrrolidines, pyrimidines, dipeptides and oligopeptides, all of which are part of the nitrogen metabolism. Results suggest that Bacillus cells reduction of TTC into triphenyl formazan (TPF) and its further accumulation inside the cells, induces the production of nitrogen-derived compounds, either by activation of nitrogen metabolism biosynthetic pathways or by a biotransformation of TPF into derivatives. Once produced, the compounds are secreted into the medium and act as antimicrobials against other bacteria.